Pengaruh Kinerja Keuangan Bank Syariah, Zakat, Pajak, dan Foreign Direct Investment terhadap Pertumbuhan Ekonomi Indonesia - Rizkyaningrum, Adinda Agustinayu; Lestari, Lisa Yuni; Febrianto, M. Nanang; Subagiyo, Rokhmat; Sholihah, Ummu (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
The Purpose of this research influence of short-term and long-term variables Return on Assets, Zakat, Taxes, and Foreign Direct Investment on Economic Growth in Indonesia 2006-2023. This research uses quantitative methods with a descriptive approach. The data source uses secondary data sourced from the Central Statistics Agency, Ministry of Finance, Financial Services Authority, and the National Zakat Amil Agency for 2006-2023. The results obtained show that in the short term the ROA, Tax, and FDI variables have a negative and insignificant impact, while Zakat has a positive and insignificant impact on economic growth. Long-term VECM testing of the ROA and FDI variables has a negative and significant effect, while the Zakat and Tax variables have a positive and significant impact on economic growth.